1998
DOI: 10.1038/bjc.1998.275
|View full text |Cite
|
Sign up to set email alerts
|

High-dose therapy including carboplatin adjusted for renal function in patients with relapsed or refractory germ cell tumour: outcome and prognostic factors

Abstract: Summary Thirty-one consecutive patients with relapsed or refractory GCT received an HDT schedule including carboplatin, the dose of which was adjusted to measured glomerular filtration rate. There was one HDT-associated death (3%), due to acute renal failure. The 3-year probability of overall and disease-free survival for 21 patients with primary refractory disease or responsive relapse was 60% and 42%, respectively, while none of ten patients with refractory relapse have survived disease free.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Previous reports (Beyer et al, 1996;Lyttelton et al, 1998), including our current data, have shown that patients with cisplatin-refractory disease have significantly poorer outcomes than those who are cisplatin sensitive. However, it is noticeable that two patients presented here with cisplatin-refractory disease have survived long term (over 44 months), one of whom was absolutely refractory.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…Previous reports (Beyer et al, 1996;Lyttelton et al, 1998), including our current data, have shown that patients with cisplatin-refractory disease have significantly poorer outcomes than those who are cisplatin sensitive. However, it is noticeable that two patients presented here with cisplatin-refractory disease have survived long term (over 44 months), one of whom was absolutely refractory.…”
Section: Discussionsupporting
confidence: 51%
“…The predicted long-term event-free and overall survivals were 29 and 39%, respectively. Such figures have largely been reproduced by other groups (Siegert et al, 1994;Flechon et al, 1999;Nichols and Maziarz, 1999), including our own (Lyttelton et al, 1998). Where patients received high-dose chemotherapy exclusively as part of first salvage treatment, survival figures are improved, with nearly 60% of patients alive at a median follow-up of 39 months (Bhatia et al, 2000).…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations